2020
DOI: 10.1159/000507635
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38mapk Reduces Adipose Tissue Inflammation in Aging Mediated by Arginase-II

Abstract: <b><i>Background:</i></b> Adipose tissue inflammation occurs not only in obesity but also in aging and is mechanistically linked with age-associated diseases. Studies show that ablation of the l-arginine-metabolizing enzyme arginase-II (Arg-II) reduces adipose tissue inflammation and improves glucose tolerance in obesity. However, the role of Arg-II in aging adipose tissue inflammation is not clear. <b><i>Objective:</i></b> This study investigated the role of Arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This mechanism has emerged as an essential factor underlying impaired endothelial functions [ 68 , 69 ]. Specifically, an increased arginase activity has been associated with endothelial dysfunction in a number of experimental models of hypertension, atherosclerosis, diabetes, and aging [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Pleiotropic Effects Of Argininementioning
confidence: 99%
“…This mechanism has emerged as an essential factor underlying impaired endothelial functions [ 68 , 69 ]. Specifically, an increased arginase activity has been associated with endothelial dysfunction in a number of experimental models of hypertension, atherosclerosis, diabetes, and aging [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Pleiotropic Effects Of Argininementioning
confidence: 99%
“…26 Recent studies have provided ample evidence, supporting that the p38MAPK signaling pathway is associated with a variety of age-related diseases. [27][28][29][30][31][32] For example, according to Moreno-Cugnon et al, the elevated p38MAPK activity was associated with neural stem cell aging. 29 Chen et al suggested that RAB7 was a protective factor for intervertebral discs, which retarded the intervertebral disc degeneration by inhibiting the p38MAPK pathway.…”
Section: Characteristics Of P38mapk Signaling Pathwaymentioning
confidence: 99%
“…In this issue of Pharmacology , Huang et al [6] report a role of Arg-II in age-associated adipose tissue inflammation by promoting IL-6 production. IL-6 is a key cytokine associated with inflamm-aging, and systemic IL-6 neutralization by a blocking antibody improves physical fitness in mice [7].…”
mentioning
confidence: 99%
“…IL-6 is a key cytokine associated with inflamm-aging, and systemic IL-6 neutralization by a blocking antibody improves physical fitness in mice [7]. Huang et al [6] showed that IL-6 mRNA and protein levels were increased in adipose tissue or in conditioned medium from peri-uterus fat tissue from old but not young mice. In contrast, both IL-6 mRNA and protein levels were significantly decreased in old Arg-II knockout (Arg-II −/− ) mice compared to age-matched wild-type mice, and less macrophage accumulation was observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation